Parenting in Digital Era: a Systematic Literature Review - Enjang Wahyuningrum; Suryanto Suryanto; Dewi Retno Suminar (Universitas Ahmad Dahlan, 2020)
AbstractÂ Parental care has a significant influence on childrenâ€™s digital technology use (OzgÃ¼r, 2016 ; Valcke, Bonte, De Wever & Rots, 2010). The purpose of this literature review is to know the characteristics of the participants of the articles, the type of measurement, the type of digital parenting and the digital parenting determinant factors. The method used is a systematic literature review. The article search was done online by using the keywords â€œdigital parentingâ€ and/or â€œparental mediation of internet useâ€. A total of 20 articles in the period of 2011-2020 were used to carry out this literature review taken from Sagehub, Science Direct, Ebscohost and Proquest Dissertation. The results of the literature review show that most of the participants in these articles are parents who have children from childhood to adolescence and come from Caucasian races. The measuring instrument used in the quantitative approach is a questionnaire on parental mediation of internet use from previous studies or a questionnaire that has been modified according to the research setting. Meanwhile, the interview method and focus group discussion were used for the qualitative approach. The types of parental mediation of internet use that appear are active parental mediation, restrictive parental mediation, monitoring parental mediation, supportive parental mediation, and co-use/co-viewing parental mediation. While the role of parental mediation of internet use is mostly a dependent variable, in several articles it acts as a predictor variable. This shows the existence of internal factors and external factors that affect parental mediation in parents. The results of this literature review can be a foothold for other researchers who are interested in conducting research on digital parenting of parents in childrenâ€™s digital technology use.Keywords: digital parenting, parental mediation of internet use, parents, adolescence